PERBANDINGAN HASIL LAJU ENDAP DARAH (LED) SEDIPLAST ESR SYSTEM DENGAN METODE OTOMATIS PADA PASIEN TUBERKULOSIS - Inggit Ismayanti; Enny Khotimah; Dian Rachma Wijayanti (Yayasan Pendidikan Medika Indonesia, 2026)
Infection and inflammation in tuberculosis patients are caused by the bacterium Mycobacterium tuberculosis. Increased fibrinogen levels cause erythrocytes to stick together and accelerate the formation of rouleaux, thereby increasing the Erythrocyte Sedimentation Rate (ESR). The Westergren method is recommended by the International Council for Standardization in Haematology (ICSH) for ESR testing. With the advancement of technology, ESR testing can now be performed using modified Westergren methods such as the Sediplast ESR System and automated methods to avoid and reduce the risk of laboratory personnel exposure to infectious agents.The aim of this study was to determine whether there was a difference in ESR results on the Sediplast Esr System using EDTA + 3.8% sodium citrate blood and the automatic method using EDTA blood in patients with active tuberculosis at the Tambora Community Health Center. This study used an analytical observational research design with a cross-sectional approach. The sample in this study consisted of 35 patients with active tuberculosis who were treated at the Tambora Community Health Center pulmonary clinic. The results of the ESR test using the Sediplast Esr System method obtained an average of 57.86 mm/hour, while the automatic method obtained an average of 52.51 mm/hour, with an average difference of 5.34 mm/hour. Statistical analysis using the Paired T Test yielded a sig value (2-tailed) of 0.025. This study shows that there is a difference in the results of the Sediplast Esr System method and the automatic method for measuring erythrocyte sedimentation rate (ESR).